Monolithic TCAD simulation of phase-change memory (PCM/PRAM) + Ovonic Threshold Switch (OTS) selector device. (January 2023) - Thesberg, M.; Stanojevic, Z.; Baumgartner, O.; Kernstock, C.; Leonelli, D.; Barci, M.; Wang, X.; Zhou, X.; Jiao, H.; Donadio, G.L.; Garbin, D.; Witters, T.; et al.
Abstract: Owing to the increasing interest in the commercialization of phase-change memory (PCM) devices, a number of TCAD models have been developed for their simulation. These models formulate the melting, amorphization and crystallization of phase-change materials as well as their extreme conductivity dependence on both electric field and temperature into a set of self-consistently-solved thermoelectric and phase-field partial-differential equations. However, demonstrations of the ability of such models to match actual experimental results are rare. In addition, such PCM devices also require a so-called selector device – such as an Ovonic Threshold Switching (OTS) device – in series for proper memory operation. However, monolithic simulation of both the PCM and OTS selector device in a single simulation is largely absent from the literature, despite its potential value for material- and design-space explorations. It is the goal of this work to first characterize a PCM device in isolation against experimental data, then to demonstrate the qualitative behavior of a simulated OTS device in isolation and finally to perform a single monolithic simulation of the PCM + OTS device within the confines of a commercially available TCAD solver: GTS Framework. Highlights: Phase-change memory (PCM) devices are important devices of commercial interest. PCM models are rarely validated against experiment. In this work a PCM model is validated against experimental pulse data. PCM devices also require "selector" devices in series which is often ignored. Here we consider a monolithic simulation of PCM+OTS selector device.